Upaya Meningkatkan Kemampuan Bahasa Anak Usia 4-5 Tahun melalui Media Cerita Bergambar di TK Qur’an Mandiri Medan - Candri Wulan Nasution; Zulfahmi Lubis (Darul Yasin Al Sys, 2026)
Language development is an important aspect of early childhood education because it plays a role in supporting children’s ability to communicate, understand information, and express ideas. However, the language ability of children aged 4–5 years still requires learning stimulation that is appropriate to their developmental characteristics, one of which is through picture story media. This study aims to identify the initial steps in implementing picture story activities, analyze children’s language development before and after the activities, and determine the improvement of children’s language ability through picture story media at TK Al Qur’an Mandiri Medan. This study used Classroom Action Research (CAR) with 9 children as the subjects. Data were obtained through the implementation of actions in two cycles and analyzed based on children’s language development achievements. The results show that in Cycle I, the use of picture story media resulted in 2 children (22.22%) reaching the Developing as Expected criterion, so the improvement in children’s language ability had not yet reached the success indicator. In Cycle II, a better improvement occurred, namely 1 child (11.11%) reached the Developing Very Well criterion and 3 children (33.33%) reached the Developing as Expected criterion, with language ability achievement of 73.88%. Thus, picture story media proved to be able to improve the language ability of children aged 4–5 years from Cycle I to Cycle II. These findings imply the importance of using visual and narrative learning media as an appropriate language stimulation strategy for early childhood.